¿Cómo lograr que el Perú se beneficie de la apertura comercial? - Loayza, Norman (2004)
Peru is currently undergoing negotiations for free trade agreements with the United States and various East Asian countries. Subscribing to these agreements will give Peru the opportunity to consolidate and deepen the process of international trade liberalization started in the 1990s. In order for Peru to take full advantage of the opportunities that international trade openness bring, it must deepen the reforms that upgrade human capital, make financial markets more accessible, promote high quality public infrastructure and governance, and reduce the regulatory burden. In all of these areas, but particularly in that of labor markets, Peru has much scope for progress.